Development Strategy of Betta Fish (Betta sp.) Business in Manado City, North Sulawesi-Indonesia - Wibisono, Maximilianus B.; Paendong, Stella M.P; Lengkong, Meilany R.; Kaunang, Stella T. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study focuses on the development of the Betta fish market in Manado City, North Sulawesi-Indonesia with the problem being the underdeveloped marketing strategy for Betta fish. Business of Betta fish in Manado City require a specific strategy to survive in the competitive business environment, especially for businesses that are seasonal and hobby oriented. This study aims to identify internal and external factors that are strengths, weaknesses, opportunities, and threats, and formulate strategies to be applied in the development of Betta fish business (Betta sp.) in Manado City. This type of research is qualitative. Data collection techniques use questionnaires and documentation. Data analysis methods use the SWOT matrix (Strengths, Weaknesses, Opportunities, Threats). In this study, the population is the Betta fish business actors totaling 10 respondents. The results show that the strategy that can be applied in the development of Betta fish business is to support an aggressive growth. This aggressive strategy focuses more on the S-O strategy (Strength-Opportunities), which is a strategy that will utilize all strengths and opportunities to continuously improve until it reaches an optimal point. Actions that need to be taken include increasing the quantity and quality of production to meet market demand, attracting consumer interest by adding more colors of Betta fish, utilizing technological and information developments in the marketing process, and collaborating with hobbyists and Betta fish enthusiasts to facilitate the marketing process